Himalayan Vultures in Khodpe, far-west Nepal: is there any threat? - Manoj Kumar Joshi; Mukesh Kumar Chalise; Anand Chaudhary; Hem Bahadur Katuwal (Journal of Threatened Taxa, 2015)
There is evidence that Himalayan Vulture Gyps himalayensis is susceptible to the veterinary drug diclofenac, which is responsible for the decline of other Gyps species across South Asia.  Unlike other Gyps species, there is little quantitative data to assess Himalayan Vultures population.  Based on observation, we analyzed the flock size and breeding success of the Himalayan Vultures on two cliffs of Khodpe in Baitadi District, far-west Nepal.  The mean flock size of Himalayan Vulture was 25.83±6.33.  Overall breeding success was 90.9% based on active nests.  We also conducted a questionnaire survey to assess the perceived threats in the view of local people to vultures and these threats include loss of food, veterinary drug, lack of proper nest sites, and lack of public awareness.  Additionally, 76% of the respondents felt that vultures were decreasing in the area, 94.7% were not aware of the toxicity of diclofenac to vultures, and very few (2%) knew about the availability of meloxicam as a safe alternative drug.  The colony we studied is one of the few remaining known breeding populations, which provide baseline information from far-west Nepal, thus we recommend for conservation and continuous monitoring of this species to understand their population change and breeding biology.